2000
DOI: 10.1164/ajrccm.162.4.9912140
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Asthma and Physiologic Outcomes in Elderly Nonsmokers

Abstract: Airway and alveolar inflammation have been described in asthma. Prolonged inflammation may lead to airway remodeling, which can result in physiologic abnormalities. Elderly lifetime nonsmokers are an ideal population in which to examine the consequences of longstanding asthma. To test the hypothesis that airflow limitation and hyperinflation are associated with the duration of asthma, we evaluated airflow and lung volumes in a cohort of elderly asthmatic individuals. All subjects were > 60 yr of age and were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 27 publications
5
50
2
1
Order By: Relevance
“…Why severe-persistent asthma of a longer duration appears to be associated with sputum eosinophilia, yet mild non-ICS treated asthma of a longer duration appears not to be, is an interesting question. A possible explanation for this apparent paradox may be that the persistence of eosinophilic inflammation may lead to the development of severe disease despite treatment with ICS, although other factors, particularly airway remodelling [29] and autonomic dysfunction [27] are important in the pathophysiological deterioration in lung function that is associated with longer asthma duration [30].…”
Section: Discussionmentioning
confidence: 99%
“…Why severe-persistent asthma of a longer duration appears to be associated with sputum eosinophilia, yet mild non-ICS treated asthma of a longer duration appears not to be, is an interesting question. A possible explanation for this apparent paradox may be that the persistence of eosinophilic inflammation may lead to the development of severe disease despite treatment with ICS, although other factors, particularly airway remodelling [29] and autonomic dysfunction [27] are important in the pathophysiological deterioration in lung function that is associated with longer asthma duration [30].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in lung function in asthma appears to be related to duration and clinical severity [199,200,[202][203][204][205]. In some studies of chronic, severe asthma, persistent airflow obstruction has been shown to be related both to inflammation, based upon exhaled nitric oxide and blood eosinophilia, and to remodelling, shown as increased wall thickness on CT scan [206].…”
Section: Fixed Airflow Obstruction and Decline In Lung Function In Asmentioning
confidence: 99%
“…Long considered a disease of childhood or young adulthood, its prevalence is now known to be similar in older people [4].…”
Section: Epidemiologymentioning
confidence: 99%
“…It is recognized as a more severe asthma phenotype with a greater degree of airflow obstruction, more frequent exacerbations, and a greater rate of lung function decline. In a study comparing patients with asthma of long duration and patients with asthma of short duration, it was found that the duration of asthma is associated with the degree of airflow limitation [4].…”
Section: Immune-senescence and Asthmamentioning
confidence: 99%
See 1 more Smart Citation